Development of a theoretical framework for the creation of assessment tools on parental literacy in child unintentional injury prevention: a literature-based expert consultation study - Kaiyue CHEN; Xiaohong LI; Jicui ZHENG; Xueqi MA; Qian ZHAO; Jingwei XIA; Jun LÜ (Editorial Office of Chinese Journal of Public Health, 2024)
ObjectiveTo analyze the research findings and development trends of parental safety literacy in relation to child injury prevention, and to establish a theoretical framework for the development of assessment tool on the parental safety literacy. MethodsThe literature, dissertations, expert consensus, and guidelines related to the assessment of unintentional injuries in children and health literacy tools published from January 1, 2002 to January 1, 2022 were retrieved from various databases including CNKI, Wanfang Dara, CQVIP, PubMed, and Web of Science. After conducting a comprehensive screening and analysis of the current state and identified shortcomings in 41 domestic and international articles concerning the assessment tools for children's unintentional injuries and health literacy, a preliminary framework for evaluating tool dimensions was established. Based on the principles of involving multiple stakeholders and achieving information saturation, a panel consisting of 18 experts was selected for group discussions or one-on-one consultations. This process resulted in the development of a preliminary framework for the assessment tool based on expert opinions. ResultsA total of 13 universal health literacy assessment tools and 28 specific health literacy assessment tools were obtained through a systematic literature search. The universal assessment tool comprehensively measures health literacy based on its definition, while the specific assessment tool focuses on measuring certain dimensions of health literacy. Consultation with 18 experts revealed that a systematic and comprehensive understanding of the concept of literacy forms the basis for evaluating parents' safety literacy, and the objective of the assessment tool for parents' safety literacy should be to identify high-risk parents. The final evaluation framework encompasses five dimensions: access, understanding, belief, communication, and utilization. ConclusionCurrently, there is a shortage of assessment tools in China that comprehensively measure parental health literacy across all dimensions. To create a complete health literacy scale suitable for application, further summarization of the assessment dimensions of the scales is necessary.